QR Tag based Verification Method for Smart IoT Applications - Al-Ghaili, Abbas M.; Kasim, Hairoladenan; Othman, Marini; Hassan, Zainuddin (2018)
A Quick Response (QR) tag based Verification Method (QRVM) used with Internet of Things (IoT) applications is proposed to verify and enable authorized requests by user to access a smart IoTbased application.QR-tag encrypted values are compared to original values. Three-layers have been proposed to attain security objectives. The first layer relates to the IoT-based application’s integrity by performing a verification procedure to QR-tag’s contents. The second layer concerns the availability whereas user’s information are stored in offline database to disable any access caused by threats.The third one periodically generates an authenticated QR tag using 1-session private key to prevent both information leakage to attain it confidential.The QRVM aims to increase the IoTbased application privacy.The QRVM contribution is that it is useful to verify requests that need permissions to access such IoT automatic access systems and smart home applications. QRVM is evaluated in terms of security factors e.g., availability. Results confirmed it is faster than other competitive methods. In addition, results discussed QRVM’s robustness against unauthorized access’s attempts and brute force attack.